Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Konservatisme Akuntansi (Studi Kasus Pada Perusahaan Manufaktir Sub Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia) - Kustanti, Eka Lasiana; Wahyu Istanti, Sri Layla (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
The objective of this study was to show the impact of profitability, leverage, and company size on accounting conservatism in Indonesian stock exchange-listed manufacturing companies in the textile and garment sub-sectors from 2019 to 2021. The dependent variable of this study was accounting conservatism, and the independent variables were profitability, leverage, and company size. The population used was 24 manufacturing companies in the textile and garment sub-sector on the Indonesia Stock Exchange from 2019 to 2021, obtained from the website www.idx.com. The documentation method was used to collect data for the research. The purposive sampling method was used during the sample selection. The research sample comprised 17 companies and 51 observations. Multiple linear analysis techniques were used to analyze the data. Before the regression, the data was tested using the classical assumption test to obtain the Best Linear Unbiased Estimate (BLUE). According to the findings of hypothesis testing, profitability had a significant positive effect on accounting conservatism, whereas leverage had an insignificant positive effect. And company size had a negative and insignificant impact on accounting conservatism. The result of determination test in this study yielded an adjusted RÂ² value of 24.4%, with the remaining 75.6% explained by factors beyond the research model.